Impact of Ragi Based Food Supplement on The Nutritional Status of Selected Preschool Children - Nagammal K (Department of Home Science, College of Agriculture, 1989)
A study on the impact of ragi based food supplement on the nutritional status of selected preschool children was conducted in the rural areas of Trivandrum district. As a first step, a survey to assess the dietary pattern of the preschool children with special reference to the influence of supplementary feeding and their food preference was conducted among 150 households using interview method .